Отражение плоских упругих волн в однородном изотропном волноводе - Н. Д. Погосян (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
In the paper the plane longitudinal and transverse (shear) waves reflection from waveqidepartition x=0 are considered in different cases of conditions on boundary x=0.
Keywords: Mechanics of deformable solids; Generalities, axiomatics, foundations of continuum mechanics of solids; Waves